The economic contribution of CGIAR germplasm health units to international agricultural research: the example of rice blast disease in Bangladesh - Enriquez, Y.; Smale, M.; Jamora, Nelissa; Hossain, M.; Kumar, P. Lava (Consultative Group on International Agricultural Research, 2022)
This study measures the economic contribution of International Rice Research Institute’s (IRRI) Germplasm Health Unit (GHU) to a breeding program that aims to avert yield losses from rice blast disease (Pyricularia oryzae Cavara) in Bangladesh. We first conceptualize the general pathways through which SHU contributes to the impact of international agricultural research. Then we use a farm-level panel dataset collected between 2013 to 2016 and data on blast incidence collected from field surveys in 2011 to 2012 to conduct an ex-ante economic surplus analysis in a productivity maintenance framework. We then apportion the incremental benefit contributions of the SHU by discounting and applying a time-saving multiplier. To address uncertainties in our estimates, we augment our model with Monte Carlo sampling to simulate distributions of model parameters. Simulating for the most probable outcome, our model estimates about USD 295 million net benefits over a 20-year time frame of continuous blast resistance breeding and deployment. About USD 5.9 million of the net benefits from the development of blast resistant rice varieties in Bangladesh could be attributed to the contribution of the IRRI GHU. The benefit-cost ratio of GHU on this breeding program alone is estimated at 112. The results are sensitive to the rate of yield savings, which is contingent on yield levels, timing of deployment, effectiveness of resistance, and lifespan of resistance to blast. The study reinforces the important, and often overlooked, role of the SHU in the international scientific partnership that aims to enhance genetic gains in rice through efficient and timely access to clean and healthy germplasm.